Economic Integration of the Czech Republic and Slovakia since the Breakup of Czechoslovakia until the Accession to the European Union - Filip Křepelka (LeXonomica, 2021)
Discussions: Economic Integration of the Czech Republic and Slovakia since the Breakup of Czechoslovakia until the Accession to the European Union